O cinema brasileiro no Festival de Cannes (1949-2017): políticas de internacionalização e abertura de mercado - Figueiró, Belisa Brião (Universidade Federal de São Carlos, 2023)
This research investigates cinematographic policies aimed at the diffusion and promotion of films at the Cannes Film Festival through a comparative study, from 1949 to 2017. For this, it carries out a survey of the Brazilian feature films selected for the Official Competition and the parallel selections. It starts from the hypothesis that the Cannes Film Festival is the arena for the main international filmmakers and whose reception and eventual awards will determine the career of its director and of the film, since this showcase can open or close the doors for exhibitions in other smaller festivals and in the commercial theater circuit, in Brazil and abroad. Based on our mapping of films, historiographical research and interviews with industry agents, it seeks to understand when internationalization policies existed that supported selection, promotion and diffusion at the festival; what were the conditions of that support; and how filmmakers arrived at the festival when there was no official support. At the same time, it analyzes the impact of technological transformations on the chosen films, the reception of the French press and the dynamics of market agents in the Marché du Film. In this context, it was found that, despite efforts and official discourse, such policies (when they existed) were not enough to effectively contribute to the advancement of this process, with the exception of some specific periods.
Brazilian cinema at the Cannes Film Festival (1949-2017): internationalization policies and new markets
Le cinéma brésilien au Festival de Cannes (1949-2017) : politiques d’internationalisation et ouverture du marché
Keywords: Festival de Cannes; Cinema brasileiro; Estado; Internacionalização; Tecnologia cinematográfica; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA::ADMINISTRACAO E PRODUCAO DE FILMES